The importance of compassionate care - Lindow, Rebecca; Gisch, Mikaela; Marchini, Leonardo (Brazilian Dental Science, 2023)
Recently, studies have highlighted the importance of compassionate care in healthcare. Not only does it improve patient outcomes and satisfaction, but it also improves the healthcare providers’ overall well-being. Furthermore, it helps streamline the healthcare system by shortening hospital stays and rates or readmittance. Unfortunately, patients report that they feel there is a lack of compassionate care provided to them, thus shedding light on the compassion crisis. The compassion crisis seems to have its roots in healthcare professional education, as evidenced by the high levels of burnout experienced by students, particularly in dental students. Compassion training, however, not only equips healthcare professionals with strategies to more effectively treat their patients, but also with coping mechanisms to better handle the stressors of their profession. Dentistry is no exception and has some unique barriers to care as well such as communication, the physical barrier during treatment. This further highlights the importance of compassionate care while providing treatment. Implementing compassionate care to be taught in school will improve patient outcomes and provider well-being.KEYWORDSEmpathy; Delivery of healthcare; Dental education; Compassion; Compassionate care.